1999
DOI: 10.1098/rspb.1999.0905
|View full text |Cite
|
Sign up to set email alerts
|

Zinc tolerance and hyperaccumulation are genetically independent characters

Abstract: The hyperaccumulation of metals by a rare class of plants is a fascinating and little understood phenomenon. No genetic analysis has been possible since no intraspeci¢c variation is known for this character. Here, we report on crosses between the zinc-hyperaccumulating and -tolerant species Arabidopsis halleri and the non-hyperaccumulating, non-tolerant species Arabidopsis petraea. The F 2 segregates for both characters and it appears that the two characters are genetically independent. The data for tolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
148
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(155 citation statements)
references
References 19 publications
5
148
0
2
Order By: Relevance
“…petraea (A.l. ), Macnair et al (1999) demonstrated that Zn tolerance and Zn hyperaccumulation are two genetically independent characters. Moreover, by comparing Zn tolerance and Zn hyperaccumulation abilities of several populations of A. halleri originating from contaminated and uncontaminated areas, Bert et al (2000) showed that both characters are constitutive properties of the species, but that populations from uncontaminated sites are slightly less Zn tolerant but exhibit higher Zn accumulation rates than populations from contaminated sites.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…petraea (A.l. ), Macnair et al (1999) demonstrated that Zn tolerance and Zn hyperaccumulation are two genetically independent characters. Moreover, by comparing Zn tolerance and Zn hyperaccumulation abilities of several populations of A. halleri originating from contaminated and uncontaminated areas, Bert et al (2000) showed that both characters are constitutive properties of the species, but that populations from uncontaminated sites are slightly less Zn tolerant but exhibit higher Zn accumulation rates than populations from contaminated sites.…”
mentioning
confidence: 99%
“…The genetics and the biochemical processes involved in metal uptake, transport, and storage by hyperaccumulating plants are still poorly understood, although this basic information is fundamental for the improvement of the technique (Van Der Lelie et al, 2001). Zn is one of the most important metal contaminant in industrialized countries (Nriagu and Pacyna, 1988), and numerous studies have been conducted on the species Thalspi caerulescens (Vazquez et al, 1992(Vazquez et al, , 1994Pollard and Baker, 1996;Lasat et al, 1998Lasat et al, , 2000Kü pper et al, 1999;Salt et al, 1999;Frey et al, 2000;Assunçaõ et al, 2001) and, to a lesser extent, on Arabidopsis halleri (Macnair et al, 1999;Bert et al, 2000;Kü pper et al, 2000;Zhao et al, 2000). This latter species is of particular interest because it is one of the closest relatives to Arabidopsis (Koch et al, 2001), whose genome is entirely sequenced (Meinke et al, 1998;Kaul et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperaccumulators typically have shoot-to-root metal ratios greater than 1, and their leaves often show the highest metal concentration inside specific tissues such as epidermal cells or leaf hairs and most often inside large or small vacuoles (Krämer et al, 1997;Kü pper et al, 1999Kü pper et al, , 2000Kü pper et al, , 2001Pickering et al, 2001Pickering et al, , 2003aFreeman et al, 2006b; for review, see Peer et al, 2005). Both metal tolerance and hyperaccumulation are considered prerequisites for metal hyperaccumulation in plants, and these molecular mechanisms have been found to be under independent genetic control (Macnair, 1993;Macnair et al, 1999;Bert et al, 2000;Assuncao et al, 2001).…”
mentioning
confidence: 99%
“…The variation of metal concentrations in orogenic soils has resulted in many local populations of widespread plant species with genetically determined metal-specific resistance levels, the best studied being in Silene vulgaris (Schat et al, 1996), but also recently demonstrated for the Zn-hyperaccumulator Arabidopsis halleri (Macnair et al, 1999). Therefore, it is not surprising that the metal uptake and resistance of the French population of T. caerulescens are distinct from the other populations studied by Lombi et al (2000) : it is simply a confirmation of a general ecological rule that widespread plant species consist of ecologically and physiologically differentiated local populations.…”
mentioning
confidence: 99%